2021
DOI: 10.4102/safp.v63i1.5337
|View full text |Cite|
|
Sign up to set email alerts
|

Malnutrition in children under the age of 5 years in a primary health care setting

Abstract: In this study, we outlined the types of malnutrition amongst children, the causes of malnutrition intervention at the primary health care level and some recommendations to alleviate childhood malnutrition in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
1
20
0
3
Order By: Relevance
“…Age is an essential risk factor for malnutrition. Malnutrition in children under five years is caused by a complex combination of food and healthcare service availability, accessibility, and utilisation (Govender et al, 2021). This current study revealed that HM was more common in toddlers (50.9%).…”
Section: Discussionmentioning
confidence: 53%
“…Age is an essential risk factor for malnutrition. Malnutrition in children under five years is caused by a complex combination of food and healthcare service availability, accessibility, and utilisation (Govender et al, 2021). This current study revealed that HM was more common in toddlers (50.9%).…”
Section: Discussionmentioning
confidence: 53%
“…The literature shows that burden of malnutrition is significant in South Asia and Africa. [16][17][18] In this study, prevalence of primary malnutrition was noted among 59.6% children studied. Data from India shows that 43.5% children below 5 years of age have under-nutrition.…”
Section: Discussionmentioning
confidence: 94%
“…This is because at this time the occurrence of brain development and intelligence will affect in adulthood. In addition, childhood is also a vulnerable period, because at this time if a child lacks nutritious food, it will be very easy to suffer from diseases and other health problems (Govender et al, 2021;Khan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%